Efektifitas Outbond dalam Meningkatkan Motivasi Belajar Siswa Pasca Pandemi Covid 19 - Marnis Susanti; Desyandri Desyandri; Irdamurni Irdamurni (Universitas Batanghari Jambi, 2023)
Covid-19 has become a major topic in public health in this world. How not, this one virus affects all aspects of people`s life activities in this world. Ranging from the political, economic, social, cultural, religious, and educational sectors. One of the aspects discussed in this article is in education. Education around the world is undergoing changes in terms process that is carried out. This of course affects the development of student learning. One of them occurs in education in Indonesia. In the beginning, learning was done face-to-face, until finally the spread of covid-19 has hit various countries incluiding Indonesia. This has resulted in a change in the learning system from face-to-face to online learning. This certainly affects learning pattens for teachers as well as students in improving their learning outcomes. Therefore, after covid-19, the goverment and teachers implemented a learning system to increase larning motivation. On of the things that is done in increasing learning motivation is through learning with its location, namely Outbound. Learning through outbound aims to increase students` enthusiasm for learning so that the expected results are achieved well.